2008
DOI: 10.1038/sj.onc.1211041
|View full text |Cite
|
Sign up to set email alerts
|

G2/M checkpoint stringency is a key parameter in the sensitivity of AML cells to genotoxic stress

Abstract: Acute myeloid leukemia (AML) cells exposed to genotoxic agents arrest their cell cycle at the G2/M checkpoint and are inherently chemoresistant. To understand the mechanism of this chemoresistance, we compared the ability of immature CD34 þ versus mature CD34À AML cell lines (KG1a and U937, respectively) to recover from a DNA damage-induced cell cycle checkpoint in G2. Here, we report that KG1a cells have a more stringent G2/M checkpoint response than U937 cells. We show that in both cell types, the CDC25B pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…One hypothesis could be the existence of still undefined function(s) of Plk1 during the G 1 phase of the cell cycle. Interestingly, we observed that in the KG1 leukemic cell line, concentrations of Plk1 inhibitor that completely inhibit cell proliferation did not induce a complete block in G 2 /M, as can be induced with DNA damaging agents like VP-16 for instance, 41 but rather a mixture of G 1 and G 2 /M cell populations (Fig. 4).…”
Section: Hypothesis To Explain the Functional Relationship Between Plmentioning
confidence: 89%
“…One hypothesis could be the existence of still undefined function(s) of Plk1 during the G 1 phase of the cell cycle. Interestingly, we observed that in the KG1 leukemic cell line, concentrations of Plk1 inhibitor that completely inhibit cell proliferation did not induce a complete block in G 2 /M, as can be induced with DNA damaging agents like VP-16 for instance, 41 but rather a mixture of G 1 and G 2 /M cell populations (Fig. 4).…”
Section: Hypothesis To Explain the Functional Relationship Between Plmentioning
confidence: 89%
“…These data are shown in Fig. 4A, together with the phospho-H2AX levels and the sensitization factor (SF), which is a ratio between the IC 50 for ara-C alone and in combination with UCN-01 (31). They confirm that, as observed in a clinical setting, complex karyotype samples are more resistant to ara-C treatment than normal ones (mean IC 50 , 9.8 nmol/L ± 0.6; n = 5 versus 5.9 nmol/L ± 0.4; n = 4; *, P = 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…At the G1/S checkpoint, DNA synthesis is inhibited, whereas intra-S phase arrest blocks mitotic entry until the S-phase is completed [30]. Finally, at the G2/M checkpoint, damaged cells are arrested in order to allow for cell repair or apoptosis [49]. CDC25s are inactivated by checkpoint kinases (CHK1 and CHK2) in an ataxia-telangiectasia mutated (ATM) and AT and Rad3-related (ATR) kinases-dependent manner.…”
Section: Cell Cycle Arrest and Cdc25 Inhibitionmentioning
confidence: 99%